Algo sobre Hölderlin sobre o Estado - Beckenkamp, Joãosinho (Revista Eletrônica Estudos Hegelianos, 2024)
At a time increasingly dominated by the idiótis, one gets shocked when comes across a statement by Hölderlin as a motto in a book of Friedrich Hayek: “What has always made the state a hell on earth has been precisely that man has tried to make it his heaven.” What? Hölderlin, a precursor of neoliberalism? Situating this statement of Hyperion in its proper context, while also presenting what Hölderlin thinks about the State, the present text shows that what makes possible an expropriating appropriation of Hölderlin’s criticism towards utopian expectations about the State is an essential ambiguity in the use of some terms: a confusion about two fundamental dimensions of the social existence of men, namely, the political and the economic. Such ambiguity, which permeates the entire liberal ideal from its beginning to the present day, is sustained by a very simplistic and false dichotomy opposing the State as permanent threat of oppression to the poor citizens, who must fight tooth and nail for their rights.